GBP2 promotes podocyte pyroptosis and contributes to the pathogenesis of pediatric lupus nephritis - Yu Sun; Jiahui Wei; Yanjun Zhao; Xingbo Jiang; Chao He; Xianhui Huang; Fengying Lei; Yuanhan Qin (PLoS ONE, 2026)
Background Lupus nephritis (LN), a prevalent and serious manifestation of systemic lupus erythematosus, exhibits particularly high incidence in children, yet its pathogenesis remains incompletely elucidated. This study aimed to investigate differentially expressed genes in LN and elucidate their regulatory mechanisms. Methods Bioinformatics analysis was conducted on the publicly available glomerular gene expression dataset GSE32591 from the Gene Expression Omnibus to identify hub genes. Based on this screening, Guanylate-binding protein 2 ( GBP2 ) was selected for further investigation. In vivo, GBP2 expression was assessed in renal tissues from pediatric LN patients by immunohistochemistry. In a murine LN model, the expression levels of GBP2 and key pyroptosis-associated markers were evaluated using immunohistochemistry, RT-qPCR, and western blotting. In vitro, a podocyte pyroptosis model was induced by lipopolysaccharide and adenosine triphosphate treatment. Functional experiments involving Gbp2 knockdown and overexpression, followed by a rescue experiment where absent in melanoma 2 ( Aim2 ) was overexpressed in Gbp2 -knockdown cells, were performed to elucidate its role and underlying mechanisms in regulating pyroptosis. Results Bioinformatics analysis identified OAS1 , OAS2 , IRF7 , GBP2 , and GBP1 as hub genes. An upregulation of GBP2 and gasdermin D (GSDMD) was observed in the glomeruli of children with LN, showing a strong correlation with 24-hour urinary protein excretion. Renal tissues from LN mice exhibited markedly increased expression of GBP2, AIM2, Caspase-1, and GSDMD compared to controls. Following siRNA-mediated knockdown of Gbp2 in vitro, a consequent reduction was observed in pyroptosis-associated proteins (GSDMD, AIM2) and diminished secretion of the pro-inflammatory cytokines IL-1β and IL-18. Conversely, Gbp2 overexpression aggravated these effects. Pyroptosis suppressed by Gbp2 knockdown was partially restored upon concurrent overexpression of Aim2 . Conclusion Our results demonstrate that GBP2 expression is significantly upregulated in LN and promotes podocyte pyroptosis, likely contributing to renal injury. These findings suggest that GBP2 facilitates the progression of pediatric LN by activating the pyroptotic pathway and triggering the release of inflammatory cytokines.